Moment-to-moment changes in feeling moved match changes in closeness, tears, goosebumps, and warmth: time series analyses. Issue 1 (2nd January 2018) - Schubert, Thomas W.; Zickfeld, Janis H.; Seibt, Beate; Fiske, Alan Page
ABSTRACT: Feeling moved or touched can be accompanied by tears, goosebumps, and sensations of warmth in the centre of the chest. The experience has been described frequently, but psychological science knows little about it. We propose that labelling one's feeling as being moved or touched is a component of a social-relational emotion that we term kama muta (its Sanskrit label). We hypothesise that it is caused by appraising an intensification of communal sharing relations. Here, we test this by investigating people's moment-to-moment reports of feeling moved and touched while watching six short videos. We compare these to six other sets of participants' moment-to-moment responses watching the same videos: respectively, judgements of closeness (indexing communal sharing), reports of weeping, goosebumps, warmth in the centre of the chest, happiness, and sadness. Our eighth time series is expert ratings of communal sharing. Time series analyses show strong and consistent cross-correlations of feeling moved and touched and closeness with each other and with each of the three physiological variables and expert-rated communal sharing – but distinctiveness from happiness and sadness. These results support our model.